Shared Leadership of Teachers through their Interpersonal Communication Competence - Nedzinskaitė-Mačiūnienė, Rasa; Merkytė, Simona (Acta Paedagogica Vilnensia, 2019)
This paper examines how the interpersonal communication competences of teachers can predict their shared leadership. The empirical research for this paper was undertaken with teachers working at lower and upper secondary schools in Lithuania. The conducted regression analysis revealed that interpersonal communication skills have a significant predictive power for the shared leadership behavior of teachers. Specifically, the study uncovered that the dimensions of interpersonal communication competence, such as clarity, credibility, and familiarity, have an important positive relationship with shared leadership. The results emphasize a need to focus on the development of teachers’ interpersonal communication, stimulating shared leadership in teacher communities. The theoretical and practical implications of teacher leadership and their communication are discussed in this paper.
Keywords: teacher; shared leadership; interpersonal communication; competence